Catheter Associated Urinary Tract Infections – A Guide to Assessment and Management Strategies - Tanwar, Priyanka; Mamta Naagar; Manish Kumar Maity (Asian Journal of Pharmaceutical Research and Development, 2024)
One of the most frequent diseases that patients in healthcare institutions get is a urinary tract infection linked to the use of an indwelling urine catheter. The length of catheterisation is a crucial factor in the development of bacteriuria, as biofilm eventually forms on all of these devices. Despite the low percentage of bacteriuric people who have symptoms, the high frequency of indwelling urinary catheter usage indicates that these infections are responsible for a significant burden of disease. About 20% of incidents of healthcare-acquired bacteremia in acute care facilities and more than 50% in long-term care facilities are caused by catheter-acquired urine infections. Limiting the use of indwelling catheters and, when required, stopping their use as soon as it is clinically practicable are the most effective ways to avoid bacteriuria and infection. Healthcare institutions' infection control systems must put methods in place and keep an eye on them in order to reduce catheter-acquired urinary infections. These tactics include monitoring catheter use, ensuring that indications are suitable, and keeping an eye out for problems. At the end, developing catheter materials that inhibit biofilm formation through technological advancements will be necessary to prevent these infections.